KEBERADAAN BAKTERI Vibrio parahaemolyticus PADA UDANG YANG DIJUAL DI RUMAH MAKAN KAWASAN PANTAI PANGANDARAN - Retno Widowati (Fakultas Biologi Universitas Nasional, 2008)
Vibrio parahaemolyticus is a bacterium in the same family as those that cause cholera. It lives in brackish saltwater and cause gastrointestinal in human. When ingested, V. parahaemolyticus causes watery diarrhea with abdominal cramping and vomiting fever. Most people become infected by eating raw or undercooked sea food i.e. shrimps. This organism can cause an infection in the skin when an open wound is exposed to warm seawater. This research investigated V. parahaemolyticus in frozen raw shrimps which sold at sea food restorants at Pangandaran Beach area. The results showed that no one of frozen raw shripms sample were contaminated by V. parahaemolyticus. But 16 of 20 frozen raw shrimps sample were contaminated by halophilic Vibrio. More attention should be paid to food sanitation at the market place, especially during handling, preparation, and cooking of the oysters.